Two validations in Baccharis (Asteraceae: Astereae) - Deble, Leonardo Paz; Oliveira-Deble, Anabela Silveira de (Balduinia, 2014)
In this paper are made the validations of Baccharis lymanii and B. nebulae. Comments, geographic distribution and allied taxa of these species are given.